PENERAPAN MODEL PEMBELAJARAN AKTIF TIPE CARD SORT TERHADAP HASIL BELAJAR IPS PADA SISWA KELAS IV - Maesya Nur Zuina; M. Hosnan; M. Taufik (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
Social studies tends to more memorize the subject matter which is quite extensive and broad in scope. In addition, social studies is less concerned with students’ thought processes and less including learning activities which can trigger students to be active. Thus, it caused the learning outcomes were less optimal. This study aims to determine the differences between learning outcomes of social science students who used active learning models card sort type with students who used conventional learning models at SDN Cikande 3. The research method used was quasi-experimental with nonequivalent control group design. Based on t-test calculation obtained tcount = 2,354 dan ttable = 2,020 with significance level 5% which means tcount > ttable (2,354 > 2,020), then Ho is rejected and Ha is accepted. That means there is a difference between learning outcomes of social science for students who use active learning models card sort type with students who use conventional learning models.